The Poverty Police: Police-Proxy University Services and Homelessness - Lynn LaCroix (Atlantis)
This paper argues for forming a working group composed of peoples with intersectional, lived experiences of homelessness. The purpose of this group is to consult on implementing the recommendations made to York University Security Services (YSS) by an expert review panel, submitted in December of 2022 in Toronto, Canada. This paper also argues against empowering YSS with the Special Constable provision of the Comprehensive Ontario Police Services Act—a central matter under discussion by the expert review panel. Grounded theory and critical discourse analysis are used in this paper to observe YSS “incident summaries,” published on YSS’s Community Safety webpage, in conjunction with an analysis of the 2022 York University Security Services Review: Final Report. The findings reported in this paper include an approximate 43% overall interaction rate between unhoused people and YSS on the York University campus and a poverty-to-criminalisation pipeline leading to the arrest of unhoused people by Toronto police. These findings give reason to reject empowering YSS with the Special Constable provision. These findings also give reason to consult peoples with intersectional, lived experiences of homelessness on policing and police-proxies, such as YSS.